Shifting epidemiological patterns and strain replacement of hand, foot, and mouth disease in southern China, 2009–2022: A longitudinal study - Yanan Hou; Huafeng Chen; Yi Jiang; Hao Huang; Zhenlian Tan; Eric J. Nehl; Hai Li; Jiangshan Wang; Jinda He; Chen Zhong; Yuqi Wang; Jian Xiao; et al. (PLoS ONE, 2026)
Background China launched a universal campaign of monovalent-inactivated EV-A71 vaccine in 2016. However, the monovalent-inactivated vaccine is ineffective against HFMD with other etiologies. To date, little is known about the epidemiological patterns and the replacement of the predominant pathogens that induce HFMD after the universal vaccination campaign. Methods Using HFMD surveillance and VP1 sequencing data in pre- and post-vaccination periods, time series analysis, and Wavelet approaches, we identified pathogen replacement, changes in the viral spectrum and epidemiological patterns of HFMD. Results A prolonged but lower peak of HFMD occurred in the spring, and a late, higher peak presented during fall in the post-vaccination period. The typical half-year transmission cycle disappeared, the one-year cycle did not change, and the CVA16 and CVA6 serotypes have the potential to replace EV-A71 as the predominant strains. Conclusions The epidemic pattern of HFMD has shifted after the vaccination campaign. While the EV-A71 vaccine reduced transmission in the spring season, it had little impact on reducing cases in fall. Meanwhile, potential new predominant strains have emerged. Public health system should incorporate enhanced surveillance by including whole genome sequencing to ensure close monitoring of serotype replacement and to assess the need for multivalent vaccines across Southern China.